Synthesis and optical studies of GdCrO3 nanoparticles - Jaiswal, Adhish; Das, Raja; Adyanthaya, Suguna D.; Poddar, Pankaj (Journal of Nanoparticle Research, 2011)
{Here we report for the first time, a detailed synthesis mechanism of GdCrO3 nanoparticles using a surfactant-less hydrothermal method. We also report a detailed study of their structural and optical properties. The selected area electron diffraction and powder X-ray diffraction studies of GdCrO3 nanoparticles show pure phase and excellent crystallinity with average particle size around 50-60 nm. The structural analysis indicates a distorted perovskite crystal structure with lattice parameter values of a = 5.3099 +/- A 0.0022
Keywords: hydrothermal; Nanoparticles; Rare earth orthochromites